Pemanfaatan Limbah Kulit Kelapa Sebagai Media Tanam Dalam Budidaya Jamur Tiram Putih (Pleurotus ostreotus) dan Jamur Tiram Cokelat (Pleurotus pulmonarius) - Ahmad Taufikur Rahman; Rahman, Ahmad Taufikur; Mahendra, Yusri; Eriyanto, Wahyu; Qomariyah, Rofi'atul; Elhany, Nurul Avidhah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2025)
One of the important biological resources in the Indonesian plantation sector is coconut. Coconut trees grow widely in several regencies in Indonesia, including Situbondo Regency. Based on data from the Situbondo Regency Statistics Agency (BPS), coconut plantation production in Situbondo Regency in 2023 reached 4.9 thousand tons. Coconut husks in Situbondo have been considered waste that is sold cheaply to prevent accumulation. Therefore, further processing or utilization is needed to provide greater productive value for coconut husks. Rarely used coconut husk waste can be an alternative to the hard-to-find sawdust media, thereby increasing productivity in mushroom cultivation, especially in the Situbondo region. This study used two types of oyster mushrooms: white oyster mushrooms and brown oyster mushrooms. Each received five treatments with three replications, resulting in a total of 15 white oyster mushroom bags and 15 brown oyster mushroom bags used. The treatment carried out was the addition of coconut fiber with different concentrations to the planting media. The planting medium that has the best influence on mycelium growth, fruit body growth time, fruit body wet weight is P1 (100% wood powder without the addition of coconut shells), while the best fruit cap diameter is obtained from the P4 treatment (75% wood powder + 25% coconut shell powder).   Keywords: Cultivation; Oyster Mushrom; Planting Media; Coconut shell